Ion-optical design of CRYRING@ESR. (26th November 2015) - Gorda, O; Braeuning-Demian, A; Danared, H; Dolinskii, A; Engstroem, M; Herfurth, F; Kaellberg, A; Kleffner, C-M; Lestinsky, M; Simonsson, A; Sjoeholm, J; Vorobjev, G
Abstract: In 2012 the CRYRING storage ring was delivered from Stockholm to Darmstadt as a part of the Swedish in-kind contribution to the FAIR project. The ring lattice has been slightly changed for optimal injection and to provide additional space for experiment equipment. For the injection from the experimental storage ring (ESR), a new transfer line has been designed. The local injector line has been significantly modified compared to the previous one in Stockholm taking into account the geometry of the existing GSI building. In this paper we present the ion-optical properties of CRYRING@ESR after the described modifications. Single-turn injection from the ESR and multi-turn injection from the local injector are discussed. Ion-optical calculations of fast and slow extraction from CRYRING are also presented. The closed orbit correction scheme is considered taking into account the future arrangement of the beam position monitors and correction magnets. Based on the results of the calculations the requirements for the magnet alignment are finally discussed.